The Effectiveness of YouTube Learning Videos in Enhancing Students' Comprehension of Procedure Text Structures: A Case Study of Fifth Grade Students - Lenny Gusti Arini; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence, 2026)
This study investigates the effectiveness of YouTube learning videos in enhancing fifth-grade students' comprehension of procedure text structures at UPT SD Negeri 064004 Medan during the 2025-2026 academic year. Initial observations revealed low student comprehension of procedure texts and insufficient variety in teaching media utilized by educators. This qualitative descriptive research involved 22 fifth-grade students who engaged with a YouTube video from the "Titiz Craft" channel titled "Creative and Unexpected Ideas from Waste Materials." Data were collected through observation, interviews with both teachers and students, documentation, and procedure text writing assessments. Results demonstrated significant improvements in student understanding, with mean scores of 84.63 (categorized as "Good"). Of the 22 students, 6 (27.27%) achieved "Very Good" category (86-100), 14 (63.63%) attained "Good" category (75-85), and 2 (9.09%) scored in the "Sufficient" category (56-74). No students fell into the "Poor" category. The findings indicate that video-based learning effectively supports students' comprehension of procedure text structures through concrete visual representation and enhanced classroom engagement